Modified Adaptive Predict Hexagon Based Search Motion Estimation Algorithm - Ali, I.; Muzammil, M.; Basit, A.; Haq, I. (The Nucleus, 2018)
Motion Estimation (ME) is a very critical part of any video encoder and different fast ME algorithms are proposed to reduce the overhead of computational cost that was available in encoding system. This paper proposes a Modified Adaptive Predict Hexagon Based Search (MAPHS) algorithm to cope the computational requirements. The proposed algorithm predicts the direction of motion by using adaptive rood shaped predictor and then Hexagonal based Search is applied to refine the search process. The adaptive predictor changes own size predetermined motion vector for each macro block. The ME process is speedup by incorporating thresholding technique, which is primarily beneficial for the videos having low motion activities. Moreover, the proposed algorithm has improved the peak signal to noise ratio (PSNR) by adaptively changing the threshold value according to the motion contents of different videos. The experimental results show that the proposed algorithm performs well on both high definition and common intermediate format videos with respect to ME time and number of search points with acceptable PSNR.